2017
DOI: 10.1007/s11789-017-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and its role in inflammation, atherosclerosis and malignancies

Abstract: Lipoprotein (a) (Lp(a)) is a modified low-density lipoprotein (LDL) particle with an additional specific apolipoprotein (a), covalently attached to apolipoprotein B‑100 of LDL by a single thioester bond. Increased plasma Lp(a) level is a genetically determined, independent, causal risk factor for cardiovascular disease.The precise quantification of Lp(a) in plasma is still hampered by mass-sensitive assays, large particle variation, poor standardization and lack of assay comparability.The physiological functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 45 publications
(92 reference statements)
2
70
0
2
Order By: Relevance
“…www.kardiologiapolska.pl Data are presented as mean ± standard deviation or number (percentage). BMI -body mass index; C1 -large-artery elasticity index; C2small-artery elasticity index; DBP -diastolic blood pressure; HDL-C -high-density lipoprotein cholesterol; LDL-C -low-density lipoprotein cholesterol; SBP -systolic blood pressure Serum LDL-C concentration -0.18 -0.13 to -0.23 < 0.01 CI -confidence interval; other abbreviations -see Table 1 www.kardiologiapolska.pl The results of our research partially coincide with those obtained by Schillinger et al [13], who showed an association between high serum concentrations of lipoprotein(a) (a modified LDL particle with strong pro-inflammatory and pro-atherogenic effects [14]) and reduced compliance of the small artery walls. In a group of subjects with atherosclerosis, the observed negative correlation between serum lipoprotein(a) and C2 was independent of other risk factors such as sex, smoking status, and diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…www.kardiologiapolska.pl Data are presented as mean ± standard deviation or number (percentage). BMI -body mass index; C1 -large-artery elasticity index; C2small-artery elasticity index; DBP -diastolic blood pressure; HDL-C -high-density lipoprotein cholesterol; LDL-C -low-density lipoprotein cholesterol; SBP -systolic blood pressure Serum LDL-C concentration -0.18 -0.13 to -0.23 < 0.01 CI -confidence interval; other abbreviations -see Table 1 www.kardiologiapolska.pl The results of our research partially coincide with those obtained by Schillinger et al [13], who showed an association between high serum concentrations of lipoprotein(a) (a modified LDL particle with strong pro-inflammatory and pro-atherogenic effects [14]) and reduced compliance of the small artery walls. In a group of subjects with atherosclerosis, the observed negative correlation between serum lipoprotein(a) and C2 was independent of other risk factors such as sex, smoking status, and diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…Many connections between the immune system and metabolism exist; acute inflammation induces hypertriglyceridemia [26], whereas chronic inflammation in the arterial walls has more complex effects, like in rheumatoid arthritis [27]. Novel approaches such as anti-inflammatory therapies like the CAN-TOS trial [13,14], T-cell-based treatments or vaccination against LDL or Lp(a) [28] could potentially reduce cardiovascular inflammation and protect against the development of atherosclerosis [29][30][31]. In addition cell-cell communication is important to maintain the inflammatory settings [32].…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence has been presented that the proinflammatory and pro-atherosclerotic effects of Lp(a) are largely attributed to different oxidation-specific epitopes (produced in response to reactive oxygen species), present in Lp(a) particles [3]. This might explain a significant change in correlation levels before and after the metformin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this chronic stress does not cause reaction such strong as the acute inflammation does, it is still involved in a development of various degenerative diseases including diabetes and cardiovascular diseases (CVD). Lipoprotein (a) [Lp(a)] levels are associated with CVD, as Lp(a) may play a role in atherothrombosis and in activation of acute inflammation [3]. It is also involved in the activation of endothelial reaction, oxidative modification and formation of foam cells, processes involved in atherosclerosis progression [3,4].…”
Section: Introductionmentioning
confidence: 99%